Evaluations of Grass Pea Relay Inter-Cropping with Wheat on Vertisol in Eastern Amhara Region, Ethiopia - Taye, Tilahun; Abiye, Wudu; Lebay, Muluken (Journal of Tropical Crop Science, 2024)
Grass peas have been cultivated in Ethiopia for a long time; they are drought-tolerant and unaffected by excessive rainfall. This study evaluated the effectiveness of grass pea relay intercropping with wheat for better production and its effect on soil moisture and fertility improvement in the Jama district, northeastern Amhara, Ethiopia. The location is mainly dominated by vertisol, a black-to-gray clay with high swelling and shrinking character. The treatments were evaluated by arranging the randomized block design.  At the tillering stage of wheat, planting grass peas on furrows and between rows with 30 cm spacing effectively contributes to soil fertility status and soil moisture. Grass pea is a legume crop that incorporates nitrogen and is also used as a cover crop that retains soil moisture. This type of planting technique is also efficient in the case of land utilization; a 1.9 ha sole cropping area would be required to produce the same yields as 1 ha of the intercropped system. Planting grass peas during the tillering stage of the wheat crop is recommended.